Is higher physical activity behaviour associated with less subsequent use of any psychotropic medication: Results of a random-effects meta-analysis of prospective cohort studies - Wolf, Sebastian; Meinzinger, Edith; Frei, Anna Katharina; Seiffer, Britta; Löchner, Johanna; Takano, Keisuke; Scarlett, Siobhan; Kenny, Rose Anne; Derhon, Viviane; Adornes Guimarães, Maria Eduarda; Schuch, Felipe Barreto (Mental Health and Physical Activity, 2024)
Physical activity is associated with lower risk of incident depression and anxiety disorders. However, there is no meta-analytic evidence on the associations between physical activity levels and the incident use of psychotropic medications. PubMed, Embase, Scopus, Web of Science, PsycINFO, and Cochrane were searched up until March 2024 to identify prospective cohort studies in the general population without age restrictions, with any sample size, and with at least one year of follow-up. Risk of bias was assessed using the Newcastle-Ottawa Scale and a random-effects meta-analysis of adjusted relative risks was performed. Three studies comprising 40,111 participants and 322,521 person-years were included (mean age 53.8, range 18–90 years; 54% women). Relative to people reporting no physical activity, those accumulating any volume of physical activity had 15.0% (95% CI: 0.76, 0.96) lower risk of any subsequent medication use. Heterogeneity was moderate and not significant (I2 = 33.6%). The current meta-analysis demonstrated that people with higher physical activity levels are at lower risk of subsequent use of psychotropic medication. However, the evidence is based on a small number of studies (n = 3), highlighting the need for high-quality longitudinal studies.
CRIS-Team Scopus Importer:2024-11-26